A Novel Sampling Model to Study the Epidemiology of Canine Leishmaniasis in an Urban Environment - Parker, Lucy A.; Acosta, Lucrecia; Gutierrez, Mariana Noel; Cruz, Israel; Nieto, Javier; Deschutter, Enrique Jorge; Bornay-Llinares, Fernando Jorge (Frontiers in Veterinary Science, 2021)
Background: The domestic dog is the main reservoir of zoonotic visceral leishmaniasis (ZVL) and a high prevalence of canine leishmaniasis (CanL) is associated with transmission of infection to humans. Here we describe the methodology used to obtain a rapid and representative sample of domestic dogs and compare the prevalence of Leishmania infection with a sample of shelter dogs. Methodology: We used the city land registry to make a random selection of homes and systematically recruited. We also included all dogs from the main canine shelter within the city. We extracted a blood sample from each dog and performed four different serological tests. Results: The seroprevalence among domestic dogs was 20.1% (95%CI 16.1 – 24.6) which was significantly lower than among the abandoned dogs (38.6, 95%CI 27.7-50.6, p<0.001). The spatial distribution of infected dogs was fairly homogenous throughout the city. Among domestic dogs, we observed a positive association between where the dog slept and presence of anti-Leishmania antibodies (p= 0.034). Of the seropositive domestic dogs 38 (54.4%) were asymptomatic. Conclusions: Our findings demonstrate how seroprevalence results can be highly influenced by sampling methodology. We demonstrate how the land registry can be used to estimate the prevalence of CanL in representative sample of domestic dogs in an urban setting, allowing decision makers to deepen their understanding the epidemiology of CanL in a timely and efficient manner for the development of plans to address both human and canine disease.